Mammalia, Chiroptera, Vespertilionidae Rhogeessa hussoni Genoways and Baker, 1996: First record for the state of Sergipe, northeastern Brazil - Mikalauskas, Jefferson S. (2011)
Universidade Federal Rural do Rio de Janeiro. Instituto de Biologia. Laboratório de Mastozoologia. Seropédica, RJ, Brasil